Strong justice - Land, Jon (Land, Jon. Caitlin Strong novel., 2010)
A Mexican girl on the run from human traffickers brings fifth-generation Texas Ranger Caitlin Strong to the sleepy border town where her legendary grandfather once worked, a region that hides a deadly weapon with a potential to give a new enemy the means to terrorize the United States.